Evaluacion de la actividad anti-infectiva de extractos de actinobacterias marinas como candidatos para el tratamiento del acne vulgar (2025)
This thesis fulfills the requirements for the Doctorate in Biosciences at Universidad de La Sabana. The work, resulting from the research journey, is structured as a compilation of research articles, either published or submitted, that address the thesis objectives. The findings related to these objectives are presented in Chapters 1 to 4. Additionally, the thesis includes a concise introduction, a comprehensive discussion, a conclusion that outlines the limitations of the study and its future perspectives and an ethical consideration statement.